Influence of antifertility agents Dutasteride and Nifedipine on CatSper gene level in epididymis during sperm maturation in BALB/c mice. Issue 4 (April 2018) - Srivastav, Archana; Changkija, Bendangla; Sharan, Kunal; Nagar, Geet Kumar; Bansode, Falgun W
Abstract : Calcium (Ca 2+ ) signaling is critical for successful fertilization. In spermatozoa, capacitation, hyperactivation of motility and the acrosome reaction are all mediated by increases in intracellular Ca 2+ through CatSper (sperm-specific cation channel). The CatSper channel complex contains four pore-forming α subunits (CatSper1–4) and five accessory subunits called β, δ, ε, γ and ζ. Genetic deletion of any of the four CatSper genes in mice results in loss of hyperactivated motility and male infertility. Despite their vital role in male fertility, almost very little is known about influence of antifertility agents on CatSper gene expression in epididymis and epididymal spermatozoa. Therefore, we performed quantitative real-time qPCR analysis for CatSper expression in the epididymis and epididymal sperm of BALB/c mice after treatment with Dutasteride (DS), a dual 5-α reductase inhibitor and Nifedipine (NF) a calcium channel blocker as positive control. We observed that treatment with antifertility agents Dutasteride and Nifedipine induced significant decreases in the caput and cauda epididymal sperm counts, motility and fertility which could partly be attributed to alteration in the normal morphology of the sperm associated with downregulation/upregulation of CatSper mRNAs in epididymis and epididymal spermatozoa of male BALB/c mice. These can be explained on the basis of interference with mechanisms affecting calcium ion signaling resulting in changes in intracellular calcium required for sperm activity, finally affecting sperm maturation and fertility of male BALB/c mice. These studies provide some novel avenues for developing new male contraceptives in future.